Answer:
B
Explanation:
Given a quadratic equation in standard form, ax² + bx + c = 0 ( a ≠ 0 )
Then the sum of the roots = -
![(b)/(a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/x6a45jobqel3im0txd7yyl536slmk0uat9.png)
A 2x² - 3x + 6 = 0
with a = 2 and b = - 3
sum of roots = -
=
≠ 3
B - x² + 3x - 3 = 0
with a = - 1 and b = 3
sum of roots = -
= 3 ← True
C
x² -
x + 1
with a =
and b = -
![(3)/(√(2) )](https://img.qammunity.org/2021/formulas/mathematics/college/qxc5j3c5agwa66kfsowc0c4td40vnqxhni.png)
sum of roots = -
=
≠ 3
D 3x² - 3x + 3 = 0
with a = 3 and b = - 3
sum of roots = -
= 1 ≠ 3
Thus the equation with sum of roots as 3 is B